Numerical Simulation of the Flow around Two-dimensional Partially Cavitating Hydrofoils - Celik, Fahri; Ozden, Yasemin Arikan; Bal, Sakir (HARBIN ENGINEERING UNIV, 2014)
In the present study, a new approach is applied to the cavity prediction for two-dimensional (2D) hydrofoils by the potential based boundary element method (BEM). The boundary element method is treated with the source and doublet distributions on the panel surface and cavity surface by the use of the Dirichlet type boundary conditions. An iterative solution approach is used to determine the cavity shape on partially cavitating hydrofoils. In the case of a specified cavitation number and cavity length, the iterative solution method proceeds by addition or subtraction of a displacement thickness on the cavity surface of the hydrofoil. The appropriate cavity shape is obtained by the dynamic boundary condition of the cavity surface and the kinematic boundary condition of the whole foil surface including the cavity. For a given cavitation number the cavity length of the 2D hydrofoil is determined according to the minimum error criterion among different cavity lengths, which satisfies the dynamic boundary condition on the cavity surface. The NACA 16006, NACA 16012 and NACA 16015 hydrofoil sections are investigated for two angles of attack. The results are compared with other potential based boundary element codes, the PCPAN and a commercial CFD code (FLUENT). Consequently, it has been shown that the results obtained from the two dimensional approach are consistent with those obtained from the others.
Keywords: boundary element method (BEM); sheet cavitation; CFD; hydrofoil; cavity closure model; 2D hydrofoils; Engineering